Aplicação de ácido ascórbico em sementes de feijão-de-corda [Vigna unguiculata (L.) Walp.] na atenuação dos efeitos do envelhecimento e do estresse salino. - Brilhante, Jean Carlos de Araújo (2011)
The main objective of this study was to evaluate the effect of exogenous application of ascorbic acid in reducing the damage caused by aging and salinity in cowpea seeds. Three experiments were conducted, and the plant material used as a template in these experiments, seeds of cowpea [Vigna unguiculata (L.) Walp.], cultivate EPACE 10, available from the Germplasm Bank of cowpea of UFC. In the first experiment, preliminary tests were made to obtain the best methodology for the application of ascorbic acid in cowpea seeds. The seeds were incubated with 0.42 and 0.85 mM ascorbic acid at different exposure times (4h, 8h and 24h) using two different methods: (I) - Soaking in germitest paper in a petri dish and (II) - Drowning in solution in the Erlenmeyer. After applying the treatments were quantified in seeds, the ascorbic acid content and then compared to the standard content of endogenous ascorbic acid existing in the control seeds (0 h). It was observed that in all treatments examined, the endogenous AsA content of the seeds of cowpea was greater than that of control seeds, which have not undergone treatment. As has been increasing the exposure time of seeds, there was a steady increase in the ascorbic acid content of seeds, with a statistically significant difference between the exposure times examined, the most efficient of 24 h. There was a significant difference in the concentrations used exogenous, being 0.85 mM of the most efficient. There was no significant difference between the methods applied at a concentration of 0.42 mM, at a concentration of 0.85 mM. At 24 h of exposure, we observed that despite the numerical value of the method (II) is superior to the method (I), we found no statistically significant difference between application methods at that time then we can conclude from the results presented that both the method of application (I) or (II) with the concentration of 0.85 mM ascorbic acid for a period of 24 h was the most efficient methodology for the application of exogenous ascorbic acid in cowpea seeds, cultivate EPACE 10. In the second experiment, as defined the methodology of exogenous application was then made to investigate the possible effect of pre-or post-treatment with ascorbic acid in reducing the harmful effects caused by aging in the cowpea seeds, through physiological and biochemists. Seeds of cowpea rope were placed in accelerated aging chamber (45 °C, 99% RH in the dark). The seeds were subjected to four treatments: (T1) and aging seeds were not treated with ascorbic acid (AsA), control (SNE); (T2) and non-aged seeds treated with AsA (SE); (T3) seeds Before aging were subjected to a pretreatment with 0.85 mM AsA (SE-Pre-T); (T4) seeds, after aging, were subjected to a post-treatment with 0.85 mM AsA (Post-SE-T). The seeds of T4 showed higher fresh weight than the control (T1). There was a reduction of almost 15% seed germination after aging for 72 h, evidenced by the treatment (T2). However, when seeds were treated with ascorbic acid solution treatment (T4) the% germination was higher than in the control (T1) in almost 13%. Seed treatment (T2) and (T3) had a higher% of membrane damage (35.16 and 36.82), respectively, measured by increased electrolyte leakage (EC) when compared with the control (T1) (17.84). The aged seeds of treatment (T2) showed a smaller force, measured by electrolyte leakage, the control (T1). T3 caused negative results in the cowpea seeds with aging for 72 h in all variables related to the vigor and germination. However, exogenous application of ascorbic acid solution 0.85 mM after aging for 72 h in the cowpea seeds alleviated the harmful effects caused by aging vigor and germination of seeds. Evidenced by a higher content of fresh and dry weight, integrity of membranes, reduced lipid peroxidation, higher percentage germination, higher percentage of seedling emergence in the field, the higher content of ascorbate and APX activity increased when compared with the T3. The results suggest that exogenous application of 0.85 mM ascorbic acid in the cowpea seeds after artificial aging (after treatment), can mitigate their damaging effects on vigor and germination of these seeds. Finally, the third experiment, we investigated the effect of exogenous application of ascorbic acid in acclimation of aged seeds of cowpea to salt stress also through physiological and biochemical parameters. Seeds were aged for 72 h in the accelerated aging chamber (45 °C, 99% RH in the dark). After germitest were sown on paper soaked with (T2) deionized water (T3) 100 mM NaCl, (T4) and 0.85 mM ascorbic acid, (T5) at 100 mM NaCl + Ac. The 0.85 mM ascorbic acid and the control (T1), aging seeds with deionized water. Sampling was done in three stages morph physiologic, when variables related physiological effect. The T2 and T3 affect the vigor with mass reduction in membrane integrity and germination. The T4 attenuated effects caused by aging on the germination and vigor, presenting a higher emergence rate index (ESI) and lower mean emergence time (MET) and higher water content. The T3 and T5 delayed the mobilization of reserves compared with the T1 and T4. The T5 has reduced the fresh weight, increased electrolyte leakage and delayed germination with a largest ESI and smallest MET. The application of ascorbic acid, was able to mitigate the effects caused by aging, but was not able to mitigate the effects of NaCl in the aged seeds of cowpea. The study of the relationship between the use of natural antioxidants, with a possible revival of aged seeds, using the cowpea as a model, can generate media strategies to enhance antioxidative defenses and mitigating the effects of stress in storage environments seed under uncontrolled conditions, mainly in small and medium-sized farms.